Distal femural fractures. Surgical options - La Floresta, Pancrazio; Miceli, Salvatore; Doronzo, Giovanni; Borri, Massimiliano (Lo Scalpello - Journal, 2020)
Distal femur fractures are complex and relatively rare. Conservative treatment has now been abandoned. The purpose of surgical treatment is to obtain an anatomical reduction of the articular surface, restoring the coronal and sagittal axis of the skeletal segment with a stable osteosynthesis, thus avoiding post-operative immobilization and allowing for early physical therapy. The literature reports similar results with different kinds of osteosynthesis: anterograde or retrograde nailing, dynamic compression screw plate, locking compression plates, and blade plates. Not only the type of fracture, but also the experience of the single surgeon should be taken into account when choosing the type of osteosynthesis.